Development of Risk Management to Sharia Insurance Business in Indonesian Market (Sainteknol : Jurnal Sains dan Teknologi, 2022)
The background of this research is the existence of several insurance companies in Indonesia whose operating licenses were closed by the Indonesia Financial Authority so that policyholders cannot receive insurance benefits. Risk Management is very important to be carried out by all insurance companies including sharia insurance because all business activities and all aspects of life contain risks. The research method used is descriptive qualitative. The results of the discussion show that risk management means that the company has analyse the risks and impacts of risks for business continuity in the future as well as how to take into account all possible risks that arise while anticipating all possibilities that will occur. The conclusion of research is risk management will make it easier for insurance companies to make short-term, medium-term, and long-term plans so that the company can run well and develop in the future so as not to harm policyholders.